Ressignification of knowledge and practice- Teaching Mental Health in Nursing graduation (Research, Society and Development, 2021)
The objective of this study is to understand the way in which the professional nurse works in the field of mental health in the post-Psychiatric Reform period, having as a subsidy their training during graduation. It is a qualitative research, with descriptive and exploratory characteristics, based on a field research, in which 8 professional nurses working at the Psychosocial Care Centers (CAPS) of the city of Juiz de Fora - MG were interviewed and administered exclusively by the city hall. Results: two topics emerged: Reflection of training in the field of action and Need to update professional acts in mental health, where we can see that training during undergraduate courses regarding mental health was incipient, with theoretical and practical content that was disjointed and decontextualized substitute services. All confirmed that they explored other materials and sources to improve and better understand the issues pertinent to mental health care during their work at CAPS. Conclusion: It was evidenced in the research that even after 20 years of Law 10.216, nurses continue to have difficulties in recognizing their praxis within the CAPS and recognize that the contents acquired during their training were not sufficient for an adequate work within the framework of the new ideology of mental health.